2010
DOI: 10.1007/s10212-009-0002-0
|View full text |Cite
|
Sign up to set email alerts
|

Parental beliefs concerning development and education, family educational practices and children’s intellectual and academic performances

Abstract: The present study examines the relationships between parental beliefs relating to development and education, parenting practices, and the intellectual and academic performances of children. Data were collected for 128 families with a child in the second or third year of primary school. Investigations of the factors affecting the children's performances were carried out using two models that combined the different study variables. Compliance between the data and the theoretical models was tested by path analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…Research has demonstrated an association between parenting beliefs and academic achievement, with authoritarian beliefs relating to poorer academic outcomes in comparison to authoritative beliefs (Aunola, Nurmi, Niemi, Lerkkanen, & Rasku-Puttonen, 2002;Burchinal et al, 2002;Davis-Kean, 2005;García & Gracia, 2009;Shumow, Vandell, & Posner, 1998;Tazouti, Malarde, & Michea, 2010). This finding has been shown even after controlling for such variables as race, socioeconomic status (SES), and level of maternal education (Shumow et al, 1998).…”
Section: Authoritarian Parenting Beliefs and Academic Achievementmentioning
confidence: 87%
See 3 more Smart Citations
“…Research has demonstrated an association between parenting beliefs and academic achievement, with authoritarian beliefs relating to poorer academic outcomes in comparison to authoritative beliefs (Aunola, Nurmi, Niemi, Lerkkanen, & Rasku-Puttonen, 2002;Burchinal et al, 2002;Davis-Kean, 2005;García & Gracia, 2009;Shumow, Vandell, & Posner, 1998;Tazouti, Malarde, & Michea, 2010). This finding has been shown even after controlling for such variables as race, socioeconomic status (SES), and level of maternal education (Shumow et al, 1998).…”
Section: Authoritarian Parenting Beliefs and Academic Achievementmentioning
confidence: 87%
“…Parental input is associated with not only structural aspects of a child's language, such as vocabulary and syntax (Barnes, Gutfreund, Satterly, & Wells, 1983;Huttenlocher, Haight, Bryk, Seltzer, & Lyons, 1991), but also the social-communicative aspects (Ely & Gleason, 1995). A number of studies have shown a significant association between parenting and language in early childhood (Burchinal et al, 2002;NICHD ECCRN, 2004;Raviv, Kessenich, & Morrison, 2004;Tazouti et al, 2010;Topor et al, 2010), but these studies failed to clarify the predictive role of parenting beliefs on later language development. Parenting beliefs could be associated with a child's language development as a consequence of the different patterns of parent-child interactions a parenting style encourages.…”
Section: Authoritarian Parenting Beliefs and Academic Achievementmentioning
confidence: 96%
See 2 more Smart Citations
“…Accordingly, they will show greater interest, as well as positive beliefs and attitudes, concerning STEM [66]. Such positive attitudes and beliefs may be related to children's numerical competencies [67][68][69].…”
Section: Direct Links Between Parents' Stem Occupations and Children's Numerical Competenciesmentioning
confidence: 99%